Representations of Identity and Difference in Al-Khudair’s Journey to the Comoros - Ali, Yassin; Alhumam, Anas (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to reveal the representations of identity and difference in a recently released travel text by Saudi writer Abdullah Al-Khudair, entitled (kartala-flavored strangeness-a journey from Al-Ahsa to the Comoros), in which the writer recorded his trip to the Comoros, carrying the pleasure of self-discovery by looking at it in the mirror of the other, and the pleasure of discovering the different other. Methods: The approach adopted for reading in this blog is a cultural approach that provides the researcher with mechanisms that enable him to research the civilizational problems resulting from meeting the other, and to study the representations formed from this meeting in the studied literary discourse. Results: The study revealed an important presence of representations of identity in this travel text, which emerged through the writer’s evocation of the memory of place, symbols, traditions, and cultural norms. The study also showed the presence of representations of the African other, revealing the ability of the studied blog to break the stereotyped image of the culture represented by the new images and representations it presented of it which differ from the ones we have described in many other blogs. Conclusions: The bottom line is that this travel text represents an important window on an area that has not found its share of attention in Arab Studies, and it gains its importance from its ability to carry the discourse of identity, evoking the problem of the self and the other in a different civilized space, and approaching the issue of images that concern the image of another people. This is why we recommend the need to open up to this area by writing about it and studying its literature.